2018
DOI: 10.1021/acs.energyfuels.7b04137
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Pore Size Distribution of Different Indian Shale Gas Reservoirs for Gas Production and Potential CO2 Sequestration

Abstract: A thorough knowledge on pore size distribution (PSD) is one of the fundamental requirements for characterization of shale gas reservoirs and for accurate estimation of their gas storage potential. However, being an important future source of energy need in India, the pore size distribution of Indian shale gas systems is not scientifically well understood. In the present study, the nanoscale pore size distributions of prospective Indian shale basins, viz., Cambay, Cauvery, Krishna-Godavari (K-G), and Damodar va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…It meant BPRS had the most active adsorption sites, followed by BPR, and finally BP. The pore sizes of micropore, macropore, and mesopore were defined as less than 2 nm, greater than 50 nm, and between 2 and 50 nm, respectively [49]. As mesopore was conducive to the distribution of active sites of the adsorbent, it increased the contact between active sites and the adsorbate, which was beneficial for adsorption [50].…”
Section: Characterizationmentioning
confidence: 99%
“…It meant BPRS had the most active adsorption sites, followed by BPR, and finally BP. The pore sizes of micropore, macropore, and mesopore were defined as less than 2 nm, greater than 50 nm, and between 2 and 50 nm, respectively [49]. As mesopore was conducive to the distribution of active sites of the adsorbent, it increased the contact between active sites and the adsorbate, which was beneficial for adsorption [50].…”
Section: Characterizationmentioning
confidence: 99%
“…An increase in permeability and CO 2 adsorption with either increasing TOC or illite content was concluded. Some studies indicated that TOC increases with higher thermal maturity [22]. TOC (thermal maturity) and clay minerals (illite, muscovite, and kaolinite) content representing the organic and inorganic adsorbing components of gas shales can be another set of parameters for prescreening criteria.…”
Section: Criteria For Prescreening a Shale Reservoir Candidate For The Cs-egrmentioning
confidence: 99%
“…These methods are generally used to estimate the number of parameters that are otherwise technically or theoretically challenging to obtain 29 , 30 . The data-driven approaches have been used in various disciplines of the industry, such as approximation of multiple parameters related to carbon capture and sequestration 31 , 32 , predicting oil recovery 33 . And estimation of rock and fluid properties 32 , 34 36 .…”
Section: Introductionmentioning
confidence: 99%
“…The data-driven approaches have been used in various disciplines of the industry, such as approximation of multiple parameters related to carbon capture and sequestration 31 , 32 , predicting oil recovery 33 . And estimation of rock and fluid properties 32 , 34 36 .…”
Section: Introductionmentioning
confidence: 99%